Evaluation of spray coverage by high-and low-volume sprayers in greenhouse tomatoes - Chatzigiannis, Dimitris (Department of Agricultural Sciences, Biotechnology and Food Science, Faculty of Geotechnical Sciences and Environmental Management, Cyprus University of Technology, 2021)
Tomato (Solanum lycopersicum L.) is one of the most important greenhouse crops worldwide. In Cyprus, tomato is the second most important vegetable crop with an annual value exceeding 12 million euros. To protect their crop, farmers spray with plant protection products (PPP’s) during the growing season to control pests and diseases. The most common spraying application techniques in Cyprus are the motorized High Volume Sprayer (HVS) equipped with a spray gun and in recent years the motorized knapsack Low Volume Sprayer (LVS) with the incorporation of air assistance. Four experiments in greenhouse tomatoes were conducted to determine the spray coverage achieved by HVS sprayers. In addition, in the fourth grower, sprayings were carried out with both an HVS and an LVS to compare coverage by the two types of sprayers. Water Sensitive Papers (WSP) were placed at different heights and locations in the canopy of the plants to assess spray coverage. The HVS treatments achieved a mean coverage of both leaf sides combined ranging from 40 to 55% while the LVS coverage was ca. 30%. However, the coverage obtained was not proportional to the volume applied, since the HVS applied 1500-2100 L/ha, while the LVS used less than half the spraying liquid at 640 L/ha. The HVS resulted in consistently higher upper leaf side coverage than that of the lower leaf side. In contrast, the LVS resulted in uniform coverage of both leaf sides as a result of the incorporation of air assistance. The practice of spraying every second row (single row planting) or employing a twin row planting formation, resulted in substantially lower coverage of the interior leaves of the plants. In general, spray coverage increased with the height of the leaves. The current work highlights the effect of sprayer type and management practices on spray coverage of crops.
Keywords: Spray coverage; LVS; HVS; Tomato; Greenhouse; WPS; Κάλυψη με ψεκαστικό υγρό; Τομάτες; Θερμοκήπια; HVS; LVS; WPS